Peran Pengalaman Kerja Terhadap Kinerja Pegawai Melalui Motivasi Sebagai Variabel Mediasi: Studi Pada Pegawai Kecamatan Pasean Kabupaten Pamekasan - Subijanto Subijanto; Achmat Busyairi; Nugroho Mardi Wibowo (Journal of Management and Creative Business, 2024)
This type of research is explanatory research, the research uses a quantitative approach, the research sample is 45 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To determine the description of work experience, motivation and performance of employees in Pasean District, Pamekasan Regency; 2) To find out and analyze whether work experience has an influence on employee performance in Pasean District, Pamekasan Regency; 3). To find out and analyze whether work experience has an influence on motivation in Pasean District, Pamekasan Regency; 4). To find out and analyze whether motivation has an influence on employee performance in Pasean District, Pamekasan Regency; 7). To find out and analyze whether work experience has an indirect influence on performance which is mediated by employee motivation in Pasean District, Pamekasan Regency; The results showed that: 1) Work experience has a direct significant positive effect on employee performance with an Original Sample value of 0.381; 2). Work experience has a direct and significant positive effect on motivation with an Original Sample value of 0.317; 3). Motivation has a significant positive direct effect on employee performance with an Original Sample value of 0.384; 4). Work experience has a significant positive effect indirectly on employee performance which is mediated by motivation with an Original Sample value of 0.122.